1990
DOI: 10.1002/mas.1280090603
|View full text |Cite
|
Sign up to set email alerts
|

Combined liquid chromatography mass spectrometry. Part II. Techniques and mechanisms of thermospray

Abstract: This second part in the series of reviews dedicated to liquid chromatographymass spectrometry (LCNS) covers the technology of thermospray. Transport interfaces were reviewed in the previous paper (4), and application work using thermospray interfaces will appear in the third part. The same numbering system as in Part I is adopted in this text, and application work that appeared before 1982 has been generally omitted. A general introduction to the incentives of LC-MS research and the specific difficulties of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(24 citation statements)
references
References 157 publications
(2 reference statements)
1
23
0
Order By: Relevance
“…The data discussed above show that the best results are achieved without any corona discharge, by simply vaporizing the protein solutions. At first sight this experimental arrangement seems to be very similar to that for thermospray33–35 (TS). However, clear experimental differences exist: (i) the APCI capillary temperature is higher than that employed in TS (620 K vs. 520 K); (ii) while in TS the sample is vaporized in the source under reduced pressure conditions, in the present case it occurs at atmospheric pressure and the solvent and solute are vaporized in a glass evaporator tube; (iii) while electron bombardment in TS is used in order to increase the signal intensity, in the present case it causes the complete suppression of the signal; and (iv) TS is not very effective in the analysis of biopolymers34 while the proposed approach based on the use of APCI, with and without using TEA as basic deprotonant molecule, has been successfully applied in the study of two standard proteins.…”
Section: Discussionmentioning
confidence: 52%
“…The data discussed above show that the best results are achieved without any corona discharge, by simply vaporizing the protein solutions. At first sight this experimental arrangement seems to be very similar to that for thermospray33–35 (TS). However, clear experimental differences exist: (i) the APCI capillary temperature is higher than that employed in TS (620 K vs. 520 K); (ii) while in TS the sample is vaporized in the source under reduced pressure conditions, in the present case it occurs at atmospheric pressure and the solvent and solute are vaporized in a glass evaporator tube; (iii) while electron bombardment in TS is used in order to increase the signal intensity, in the present case it causes the complete suppression of the signal; and (iv) TS is not very effective in the analysis of biopolymers34 while the proposed approach based on the use of APCI, with and without using TEA as basic deprotonant molecule, has been successfully applied in the study of two standard proteins.…”
Section: Discussionmentioning
confidence: 52%
“…The zero voltage ESI or SSI mechanism is certainly different from the thermospray mechanism which apparently begins when vaporization of the liquid results in a superheated, supersonic jet of vapor, the droplets of which contain the non‐volatile molecules 21–24. These droplets are charged positively or negatively due to statistical sampling.…”
Section: Resultsmentioning
confidence: 99%
“…As far as MS is concerned this study has confirmed the usefulness of FAB-MS for characterizing organometallic complexes both by the presence of an abundant molecular ion and by the formation of specific fragments. Since the same fragments were observed in the Frit-FAB-MS and in CAD spectra, this proves that these complexes can be identified in complex mixtures through LC/MS coupling [34] and tandem MS (MS/MS: Mass Spectromet ry/M ass Spectrometry) [35].…”
Section: Discussionmentioning
confidence: 92%